Induction of Anti-Inflammatory Cytokine Expression by Ipnv in Persistent Infection - Sandino-Garcia, A; Imarai-Bahamonde, C; Maisey-Munoz, K; Acuna-Castillo, C; Reyes-Cerpa, S; Toro-Ascuy, D; Reyes-Lopez, F; Montero, R (Academic Press, 2014)
Infectious Pancreatic Necrosis Virus (IPNV) is the agent of a well-characterized acute disease that produces a systemic infection and high mortality in farmed fish species but also persistent infection in surviving fish after outbreaks. Because viral persistence of susceptible mammal hosts appears to be associated with the modulation of anti-inflammatory cytokine expression, in this study we examined the expression levels of key pro- and anti-inflammatory cytokines in kidney and spleen of trout, as well as humoral immune response (IgM and IgT) during experimental persistent viral infection and in the acute phase of infection as a comparison. IPNV infection in rainbow trout resulted in a distinct profile of cytokine expression depending on the type of infection, acute or persistent. Levels of early pro-inflammatory cytokines, IL-1? and IL-8, did not increase in the head kidney of the fish with persistent asymptomatic infection but increased in some of the symptomatic infected fish. The antiviral cytokine IFN? was not significantly induced in any of the infected fish groups. The level of expression of the Th1-related cytokine IL-12 was significantly higher in trout with persistent asymptomatic infection than in symptomatic fish. This was also accompanied by an increase in IFN?. The anti-inflammatory cytokines IL-10 and TGF-?1 had distinct expression profiles. While IL-10 expression increased in all infected fish, TGF-?1 was only up-regulated in fish with persistent infection. All infected fish had significantly lower total IgM levels than the non-infected fish whereas IgT levels did not change. Specific and neutralizing antibodies against IPNV were not observed in acute and persistent infection except in the group of fish with the lowest degree of clinical signs. Interestingly, the lack of humoral immune response could be associated with the high expression of anti-inflammatory cytokines, which might inhibit antibody production. The balance between pro-inflammatory Th1 type cytokines and the regulatory cytokines could explain the high percentage of survival and the resolution of the inflammatory response in the IPNV-infected fish but also the establishment of viral persistence. © 2014 Elsevier Ltd.